MANAGEMENT OF THE ACTIVATION OF THE FINANCIAL POTENTIAL OF THE ENTERPRISE BASED ON TOKENISATION - TULCHYNSKA, Svitlana; FALKO, Mykyta (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article dedicated the current state of management of activation of the financial potential of enterprises in Ukraine on the basis of analysis of the total liquidity, structure of current assets and liabilities of economic entities. The authors formulate strategies for managing the activation of financial potential - activation of assets, activation of equity and liabilities, parallel activation of assets and liabilities - and their main components. Approaches to the implementation of the proposed strategies are defined, which are divided into two main types - classical and alternative. The first approach is based on traditional methods of financial management, while the second approach - alternative - proposes the introduction of the latest digital technologies, such as blockchain, and the use of online platforms to improve the efficiency of financial resource management.The article focuses on the model of the alternative approach, in particular, the process of asset tokenisation, which is considered as an innovative way of managing the activation of the financial potential of enterprises. The advantages of asset tokenisation, which allows enterprises to increase their liquidity, attract additional financial resources, and ensure greater transparency and security of operations through blockchain technology, are considered. The authors focus on the feasibility of applying tokenisation of securities in Ukraine based on the low level of development of the stock market in the country, the high level of perception of cryptocurrency in the country, the developed regulatory framework and the technical feasibility of tokenisation. The article provides a detailed algorithm of the securities tokenisation process, which can be used as a basis for further development of financial technologies in Ukraine.
Keywords: financial potential; financial potential management; tokenisation; cryptocurrency; alternative finance